PENERAPAN TEKNOLOGI AGROINDUSTRI MODERN MENGGUNAKAN MIKROKONTROLER DAN SUMBER ENERGI TERBARUKAN UNTUK PENINGKATAN PRODUKSI PADA LAHAN TIDUR DI BANTARAN SUNGAI CILEMAHABANG - Adji, Riyanto; Sen, Tjong Wan (Universitas Nusantara PGRI Kediri, 2022)
The problem that will be solved in this research is to increase the production of horticultural cultivation in the idle land of Cilemahabang riverside, Mekarmukti village, North Cikarang, Bekasi Regency. This cultivation activity is currently being carried out independently by local farmer groups, but fully supported by the Village Headman and the Bekasi District Government. The proposed solution is a combination of automation technology and irrigation systems, complemented by the application of modern agro-industry. In the hope of increasing the amount of production, minimizing land processing costs, reducing pollution, and being environmentally friendly. This is inline with the SDG's research roadmap, especially in the aspect of applying smart technology and sustainability (renewable energy). The method for developing automation prototypes and solar energy sources for water pumps uses an engineering methodology. With adaptation according to conditions of the field and species of the plant. The output of this research is a prototype design which is ready to be implemented.